Air Pollution and Respiratory Health in Megacity Delhi, India - Goyal, Pramila; Kumarb, Saurabh (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 3 No 3&4 (2016): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Pulmonary tuberculosis (PTB) and COPD are major public health problems in Delhi, India. Delhi has a very high number of monthly PTB and COPD clinic visits and it is also known for its severe air quality status. We investigated the general impact of different kinds of pollutants on PTB and COPD over time by analyzing the variation in monthly clinic visits in respiratory disease hospital during 2012 to 2016. We used the generalized additive regression model to determine the monthly periodicity of PTB and air quality in a time series, as well as assessing the relationships between meteorological variables and monthly PTB clinic visits. Meteorological parameter maximum temperature exhibited significant positive correlation (r=0.303; p <0.05), and NO2 has significant negative correlation (r=âˆ’0.4; p <0.01) with the monthly count of morbidity due to TB and COPD. Generalized additive model (GAM) involving PM 2.5, PM 10 and maximum temperature as parametric smooth term explain 69.6% variation in morbidity count with adjusted R2 of 0.43. Similarly, GAM comprising CO, O3 and Maximum Temperature as parametric smooth term explain 69.6 % deviance with adjusted R2 as 0.45. GAM containing two-way interactive parametric term of PM 2.5 and PM 10 along with meteorological variable maximum temperature explained maximum deviance 77.3% among all models in the monthly morbidity count.